The build-up, configuration, and dynamical sensitivity of the Eurasian ice-sheet complex to Late Weichselian climatic and oceanic forcing. (1st December 2016) - Patton, Henry; Hubbard, Alun; Andreassen, Karin; Winsborrow, Monica; Stroeven, Arjen P.
Abstract: The Eurasian ice-sheet complex (EISC) was the third largest ice mass during the Last Glacial Maximum (LGM), after the Antarctic and North American ice sheets. Despite its global significance, a comprehensive account of its evolution from independent nucleation centres to its maximum extent is conspicuously lacking. Here, a first-order, thermomechanical model, robustly constrained by empirical evidence, is used to investigate the dynamics of the EISC throughout its build-up to its maximum configuration. The ice flow model is coupled to a reference climate and applied at 10 km spatial resolution across a domain that includes the three main spreading centres of the Celtic, Fennoscandian and Barents Sea ice sheets. The model is forced with the NGRIP palaeo-isotope curve from 37 ka BP onwards and model skill is assessed against collated flowsets, marginal moraines, exposure ages and relative sea-level history. The evolution of the EISC to its LGM configuration was complex and asynchronous; the western, maritime margins of the Fennoscandian and Celtic ice sheets responded rapidly and advanced across their continental shelves by 29 ka BP, yet the maximum aerial extent (5.48 × 10 6  km 2 ) and volume (7.18 × 10 6  km 3 ) of the ice complex was attained some 6 ka later at c. 22.7 ka BP. This maximum stand was short-lived as the North Sea and Atlantic margins were already in retreat whilst eastern margins were still advancing up until c. 20 ka BP. High rates of basal erosion are modelled beneath ice streams and outlet glaciers draining the Celtic and Fennoscandian ice sheets with extensive preservation elsewhere due to frozen subglacial conditions, including much of the Barents and Kara seas. Here, and elsewhere across the Norwegian shelf and North Sea, high pressure subglacial conditions would have promoted localised gas hydrate formation. Highlights: Maximum ice sheet coverage was 5.5 × 10 6  km 2 ∼22.7 ka BP. The EISC grew to 7.2 × 10 6  km 3, equivalent to c. 17 m of global sea level lowering. Maximum ice extension was asynchronous - 2–5 ka later east of the main ice divide. Subglacial erosion patterns reveal potential for widespread landscape preservation. The optimal reconstruction reveals a moderately thick ice complex with nunataks.